Design and synthesis of a luminescent iridium complex-peptide hybrid (IPH) that detects cancer cells and induces their apoptosis. Issue 17 (15th September 2018) - Masum, Abdullah-Al; Yokoi, Kenta; Hisamatsu, Yosuke; Naito, Kana; Shashni, Babita; Aoki, Shin
Graphical abstract: Abstract: Tumor necrosis factor related apoptosis inducing ligand (TRAIL) triggers the cell-extrinsic apoptosis pathway by complexation with its signaling receptors such as death receptors (DR4 and DR5). TRAIL is a C3 -symmetric type II transmembrane protein, consists of three monomeric units. Cyclometalated iridium(III) complexes such as fac -Ir(tpy)3 (tpy = 2-(4-tolyl)pyridine) also possess a C3 -symmetric structure and are known to have excellent luminescence properties. In this study, we report on the design and synthesis of a C3 -symmetric and luminescent Ir complex-peptide hybrid (IPH), which contains a cyclic peptide that had been reported to bind to death receptor (DR5). The results of MTT assay of Jurkat, K562 and Molt-4 cells with IPH and co-staining experiments with IPH and an anti-DR5 antibody indicate that IPH binds to DR5 and induces apoptosis in a manner parallel to the DR5 expression level. Mechanistic studies of cell death suggest that apoptosis and necrosis-like cell death are differentiated by the position of the hydrophilic part that connects Ir complex and the peptide units. These findings suggest that IPHs could be a promising tool for controlling apoptosis and necrosis by activation of the extra-and intracellular cell death pathway and to develop new anticancer drugs that detect cancer cells and induce their cell death.